Mixed influence of COVID-19 on primary maternal and child health services in sub-Saharan Africa: a scoping review - Camara, Bienvenu Salim; El Ayadi, Alison M.; Thea, Appolinaire S.; Traoré, Fatoumata B.; Diallo, El Hadj M.; Doré, Mathias; Loua, Jean-Baptiste D.; Toure, Mabinty; Delamou, Alexandre (Frontiers in Public Health, 2024)
Introduction The COVID-19 pandemic profoundly affected the provision of and demand for routine health services in the world. The objective of this scoping review was to synthesize the influence of the COVID-19 pandemic on primary maternal and child health (MCH) services in sub-Saharan Africa. Methods The studies searched original studies reporting on the influence of the COVID-19 pandemic on primary MCH services. Four scientific databases (Pubmed, AJOL, CAIRN, CINAHL) and one gray literature database (Google Scholar) were used for this search. We also searched through the snowball citation approach and study reference lists. Results The influence of the COVID-19 pandemic on primary MCH services has been mixed in sub-Saharan Africa. Attendance at some health centers declined for antenatal care, deliveries, immunization, and pneumonia cases. Other health centers did not experience a significant influence of the pandemic on some of these services. In fact, antenatal care increased in a number of health centers. MCH service indicators which declined during COVID-19 were linked on the demand side to regulatory measures against COVID-19, the perceived unavailability of resources for routine services, the perceived negative attitude of staff in these facilities, the perceived transmission risk in primary health care facilities and the perceived anticipated stigma. On the supply side, factors included the lack of equipment in primary facilities, the lack of guidelines for providing care in the pandemic context, the regulatory measures against COVID-19 taken in these facilities, and the lack of motivation of providers working in these facilities. Conclusion This study recommends prioritizing the improvement of infection prevention measures in primary health care facilities for resilience of MCH indicators to epidemic crises. Improvement efforts should be tailored to the disparities in preventive measures between health centers. The identification of best practices from more resilient health centers could better guide these efforts.